2015
DOI: 10.1002/2014jc010401
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of sediment resuspension beneath internal solitary waves of depression

Abstract: Internal solitary waves (ISWs) of depression are common features of coastal environments and believed to resuspend sediments where they shoal. In this study, the sediment resupension process associated with ISWs propagating over a flat bed was investigated in the laboratory. The first-ever profile measurements of the three-dimensional instantaneous velocity field beneath the ISWs revealed that resuspension occurs during burst like vertical velocity events, which lift sediments into the water column, in the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
5
31
1
Order By: Relevance
“…[] provided additional insight toward the capacity of the instability to drive resuspension, as well as, simulations by Stastna and Lamb []. Aghsaee and Boegman [] parametrized the ISW‐induced resuspension by considering vertical velocity bursts, occurring behind the wave during propagation. Their approximation of the ISW‐induced shear stress is expressed as, τISW=ρ2co2[0.09ln(ReISW)0.44]2, where c o is the linear wave phase speed in a two‐layer continuously stratified water column (co2=Δρgh1h2/(ρoH)) and Re ISW is the momentum thickness Reynolds number based on the wave‐induced bottom boundary layer ( ReISW=|U2|LW/(ν(|U2|+c) where ν is the kinematic viscosity and U 2 is the horizontal ISW‐induced velocity at the bottom layer).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[] provided additional insight toward the capacity of the instability to drive resuspension, as well as, simulations by Stastna and Lamb []. Aghsaee and Boegman [] parametrized the ISW‐induced resuspension by considering vertical velocity bursts, occurring behind the wave during propagation. Their approximation of the ISW‐induced shear stress is expressed as, τISW=ρ2co2[0.09ln(ReISW)0.44]2, where c o is the linear wave phase speed in a two‐layer continuously stratified water column (co2=Δρgh1h2/(ρoH)) and Re ISW is the momentum thickness Reynolds number based on the wave‐induced bottom boundary layer ( ReISW=|U2|LW/(ν(|U2|+c) where ν is the kinematic viscosity and U 2 is the horizontal ISW‐induced velocity at the bottom layer).…”
Section: Discussionmentioning
confidence: 99%
“…Applying equation to the nonlinear internal waves observed by Quaresma et al . [], Aghsaee and Boegman [] estimated the ISW‐induced shear stress with equation to be 8.979 Pa or 8.803×103 m 2 s – 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The NLIW life cycle (i.e., evolution, propagation, shoaling, and breaking) has been well studied in two‐dimensions at field‐scale (large Reynolds number) [e.g., Vlasenko and Hutter , ; Bourgault et al ., ; Lamb and Farmer , ] and laboratory‐scale [e.g., Horn et al ., ; Boegman et al ., ]. However, NLIW dynamics are fundamentally three‐dimensional (3‐D) at turbulent scales [ Fringer and Street , ; Arthur and Fringer , ; Aghsaee and Boegman , ] and the basin‐scale [ Boegman and Dorostkar , ; de la Fuente et al ., ], where they are locally influenced by topography [ Vlasenko and Stashchuk , ; Zhang et al ., ]. Despite this three‐dimensionality, computational demands [e.g., Aghsaee et al ., ] have limited most field‐scale modeling of NLIWs to two‐dimensions (2‐D) in narrow lakes and tidal flows [e.g., Vlasenko and Hutter , ; Scotti et al ., ; Lamb and Farmer , ; Bourgault et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Some observational and experimental studies suggest internal wave induced pumping of sediments high into the water column. 8,9 Other computational and laboratory studies have worked to evaluate a critical wave amplitude and Reynolds number required for vortex shedding. 4,10 In particular, the laboratory experiments by Carr et al, 10 which involved internal solitary waves of depression, found qualitative agreement in the behaviour of vortex shedding with the two-dimensional numerical results of Diamessis and Redekopp.…”
Section: Introductionmentioning
confidence: 99%
“…Bottom shear stress calculations suggested that the strongest nonlinear internal waves were capable of suspending sediment. The laboratory experiments of Aghsaee and Boegman 9 show that the vertical velocities induced by bursting motions in the boundary layer are important factors in sediment resuspension.…”
Section: Introductionmentioning
confidence: 99%